2019
DOI: 10.2147/ott.s215628
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolomics: a promising diagnostic and therapeutic implement for breast cancer</p>

Abstract: Breast cancer (BC) is the most commonly diagnosed cancer among women and the leading cause of cancer death. Despite the advent of numerous diagnosis and treatment methods in recent years, this heterogeneous disease still presents great challenges in early diagnosis, curative treatments and prognosis monitoring. Thus, finding promising early diagnostic biomarkers and therapeutic targets and approaches is meaningful. Metabolomics, which focuses on the analysis of metabolites that change during metabolism, can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 110 publications
1
26
0
Order By: Relevance
“…Amino acids have been reported to be associated with other types of cancer in earlier reviews [ 88 , 89 , 90 , 91 ]. The amino acids identified in our meta-analyses (methionine, tryptophan and proline) were identified in previous reviews, although the direction of association is different for proline (i.e., positive association in our meta-analysis on lung cancer but inverse association for other cancer types) [ 88 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids have been reported to be associated with other types of cancer in earlier reviews [ 88 , 89 , 90 , 91 ]. The amino acids identified in our meta-analyses (methionine, tryptophan and proline) were identified in previous reviews, although the direction of association is different for proline (i.e., positive association in our meta-analysis on lung cancer but inverse association for other cancer types) [ 88 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids have been reported to be associated with other types of cancer in earlier reviews [ 88 , 89 , 90 , 91 ]. The amino acids identified in our meta-analyses (methionine, tryptophan and proline) were identified in previous reviews, although the direction of association is different for proline (i.e., positive association in our meta-analysis on lung cancer but inverse association for other cancer types) [ 88 , 90 , 91 ]. A possible explanation for the discrepancy is that different cancer types have dissimilar metabolism, therefore the association between the patient’s host protein metabolism and amino acid levels with cancer risk may differ between cancer types [ 92 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been directed towards characterization of tissues, including intensive research for new genetic or metabolic markers. Using metabolomics, markers in tissues and body fluids can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been directed towards characterization of tissues, including intensive research for new genetic or metabolic markers. Using metabolomics, markers in tissues and body fluids can be identified. Liquid chromatography tandem mass spectrometry (LC‐MS/MS) analysis is good at identifying breast cancer‐specific molecules, but it is a time‐consuming procedure, starting from preparation of the column to purifying specific components from tissue extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most widely techniques that are used to differentiation in the transcriptomic and metabolomic profiles are RNA-seq, LC-MS/MS, respectively (48,49). Over the last few years, several transcriptomic and metabolomic studies identified the variation in transcripts and metabolites profiles related with diseases such as obesity and BC compared with non-obese and healthy control cases, respectively, to understand the mechanisms of disease initiation and progression as well as to biomarker identification to deduce the onset and progression of cancer (16,20,21,(50)(51)(52)(53)(54)(55). Furthermore, other studies have performed the integration between transcriptomic and metabolomic data (14,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%